Persepsi Wajib Pajak Mengenai E-Filing dan Pengaruhnya terhadap Tingkat Kepatuhan Wajib Pajak Orang Pribadi Dalam Melaporkan Pajak - Teddy Gunawan; Eny Suprapti; Eris Tri Kurniawati (Jurnal Reviu Akuntansi dan Keuangan, 2017)
This research is aimed to examine the effect of taxpayer’s perception toward e-Filing system ofindividual taxpayer’s compliance in tax reporting. This research is associative research. Intaxpayer’s perception there are e-Filing usefulness variable, e-Filing ease variable, e-Filingcomplexcity, e-Filing security and privacy variable and e-Filing readiness. The population of thisresearch is individual taxpayer listed in Tax Office Pratam Batu. Sampling used of this researchis convenience sampling individual taxpayer who reported tax using e-Filing system. The technique of analysis data is questionnaire survey and to examine using multiple regression analysis. The result of this research are e-Filing usefulness variable, e-Filing security and privacyvariable and e-Filing readiness has effect on tax compliance in tax reported while e-Filing easevariable and e-Filing complexcity has no effect on tax compliance in tax reported.Keywords: E-Filing System, Compliance In Tax Reporting, Taxpayer’s Perception